Motivating the young minds / Siti Fatimah Abd Rahman - Abd Rahman, Siti Fatimah (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2018)
One of the crucial aspects in teaching is grasping your students’ motivation to focus in class and digesting the lessons. Whenever they are given any tasks, they will ask, “Is it one of the assessments?” or “will there be any marks given for this assignment?”. The most challenging situation as a lecturer is to motivate your students to do not just --- the required assessments, but the practices as well.